Strategy For Integrated Service Center For Women Empowerment And Children Protection In Children Prevention - Pulungan, Muhammad Syukri (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2019)
Violence in children is one of the issues that is most often found in news through electronic media and print media. Based on the results of the 2018 National Survey on Child and Youth Life Experience (SNPHAR) released by the Ministry of Women's Empowerment and Child Protection, showed that 6% of boys and 9% of girls had experienced sexual violence. 50% of boys and 60% of girls have experienced emotional abuse. Furthermore, 33% of boys and 20% of girls experience physical violence. The rise of various types of violence requires P2TP2A to be more proactive to reduce the number of violence against children in Mandailing Natal Regency. The purpose of this study is to find a picture of the strategy carried out by P2TP2A in Mandailing Natal Regency in preventing cases of violence against children. The method used is descriptive qualitative by interviewing respondents who come from P2TP2A devices Mandailing Natal Regency. The results showed that P2TP2A Mandailing Natal Regency had carried out its duties and functions based on the Standard Operating Procedures established by the Chairman of the Mandailing Natal P2TP2A Technical Team. The strategy undertaken is to conduct socialization to schools and villages to report acts of violence so that services can be provided in accordance with the needs of victims of good advocacy services, rehabilitation, health, counseling as well as complaints and assistance. The strategy carried out by P2TP2A in Mandailing Natal District has shown results but requires cooperation from various parties due to the limited facilities owned by P2TP2A